Randomised controlled trial on whether advance knowledge of prostate-specific antigen testing improves participant reporting of unprotected sex. Issue 5 (29th November 2006) - Thomsen, Sarah C; Gallo, Maria F; Ombidi, Wilkister; Omungo, Zablon; Janowitz, Barbara; Hawken, Mark; Tucker, Heidi; Wong, Emelita L; Hobbs, Marcia M
Abstract : Objectives: To determine whether the process of informing research participants that they would be tested for the presence of a biological marker of semen exposure would reduce bias in their reports of unprotected sex. Methods: A randomised trial of 210 female sex workers from Mombasa, Kenya, was conducted, where half the group had advance knowledge (via the request for informed consent) that they would be tested for prostate-specific antigen (PSA) in their vaginal fluid before they reported on sex and condom use for the past 48 h. The other half were invited to participate (via additional informed consent) in the test for PSA after they had already consented to be questioned and reported on these sexual behaviours. A trained nurse instructed participants to self-swab to collect vaginal fluid specimens, which were tested for PSA using ELISA. Results: Reporting of unprotected sex did not differ between those with advance knowledge of the test for PSA and those without this knowledge (14.3% v 11.4%, respectively; p = 0.27). Surprisingly, more women with advance knowledge (15.8%) had discrepant self reports and PSA results than women without advance knowledge (9.1%); however, the difference was not statistically significant (OR 1.9; 95% CI 0.8 to 4.5). Conclusions: Knowing that one's answers to a questionnaire could be verified with a biological marker of semen exposure did not make respondents more likely to report unprotected sex.